Peran Negara dalam Menanggulangi Radikalisme dan Terorisme : Analisis Konstitusional terhadap Kebijakan Deradikalisasi di Indonesia - Affandi Harlanda Baros; Muh. Mulyadi; Kurniati Kurniati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Radicalism and terrorism pose serious threats to national security and social order in Indonesia. In response, the state implements deradicalization policies that emphasize not only repressive measures but also preventive and rehabilitative approaches. Nevertheless, these policies require critical constitutional review to ensure their conformity with the rule of law and the protection of human rights. This study aims to analyze the constitutional foundations, the framework of positive legal regulations, and the challenges in implementing deradicalization policies in Indonesia. The research employs a normative juridical method with statutory and conceptual approaches, using library research on primary, secondary, and tertiary legal materials. The findings indicate that deradicalization policies are supported by a strong constitutional basis under the 1945 Constitution of the Republic of Indonesia, particularly regarding the state’s obligation to protect citizens and guarantee the right to security. However, their implementation remains constrained by regulatory disharmony, weak inter-agency coordination, limited institutional capacity, and socio-cultural challenges within society. Therefore, strengthening institutional synergy, adopting more contextual and humane approaches, and improving regulatory frameworks are essential to ensure the effectiveness and sustainability of deradicalization policies.